La Collection 1985-1991. - Tosatto, Guy; Château de Rochechouart (Rochechouart : Musée Départemental d'Art Contemporain de Rochechouart, 1991)
Anselmo, Giovanni ; Boetti, Alighiero ; Boltanski, Christian ; Bouillon, François ; Caramelle, Ernst ; Chaissac, Gaston ; Charlton, Alan ; Combas, Robert ; Cragg, Tony ; Fabro, Luciano ; Favier, Philippe ; Fisher, Joel ; Forg, Günther ; Frize, Bernard ; Fulton, Hamish ; Horn, Rebecca ; etc.
Frans
boek